Eco-efficiency evaluation of diesel engines fueled with diesel-biodiesel-ammonia blends using data envelopment analysis - Pehlivan, Davut; Okumus, Fatih; Kokkulunk, Gorkem (WILEY, 2026)
An experimental investigation was conducted to evaluate the emission and performance characteristics of a single-cylinder diesel engine fueled with various combinations of diesel, biodiesel, and ammonia. The test matrix covered 4 biodiesel levels (0%, 20%, 40%, and 100%) and 4 ammonia energy fractions (0%, 20%, 40%, and 60%) across three engine loads (50%, 75%, and 100%), ensuring a comprehensive exploration of dual, and triple-fuel strategies. A total of 48 distinct fuel scenarios were tested under controlled conditions. The relative efficiency of each configuration was assessed using input-oriented Constant Returns to Scale Data Envelopment Analysis (CCR-DEA), where engine efficiency was treated as the desirable output, and CO, CO2, HC, and NOx emissions were considered undesirable outputs. Out of the 48 experiments conducted, 35 scenarios exhibited full efficiency while 13 were found to be relatively inefficient. The lowest efficiency score, calculated as 0.672, corresponded to a fuel blend containing 60% diesel, 40% biodiesel, and 60% ammonia, operated at full engine load. Other low-efficiency scenarios were typically characterized by high ammonia ratios and low engine loads. The findings highlight a viable transition pathway toward carbon-reduced diesel engine operation, demonstrating that smart fuel blending and load management can significantly enhance both environmental and thermal performance.
Keywords: ammonia; biodiesel; data envelopment analysis; diesel engine; emissions; engine efficiency; multi-criteria evaluation; EMISSION CHARACTERISTICS; PERFORMANCE; COMBUSTION; DEA; Science & Technology - Other Topics; Engineering; Environmental Sciences & Ecology